PENCARIAN DATA PADA SISTEM BANK DATA NILAI MAHASISWA JURUSAN ILMU KOMPUTER MENGGUNAKAN METODE BRUTE FORCE - Esti Puri Cindona; Dwi Sakethi; Febi Eka Febriansyah (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2016)
Data Bank System is a place that is used to store data. In Computer Science Department, Data Bank System that is used to store data of studentsâ€™ score at Computer Science Department. The System of Studentsâ€™ Data Bank Score at Computer Science Department is still in manual form. Therefore, the system of Studentsâ€™ Data Bank score at Computer Science Department that is still in the manual system is developed to be digital system. In searching the system of studentsâ€™ data bank Score at Computer Science Department in digital form by applying Brute Force algorithm. Brute Force algorithm is a string searching algoritm which is used each character checking method in pattern with every character in the text. Data searching in the System of Studentsâ€™ Data Bank Score at Computer Science Department the testing was done with some caseÂ tests that focused on functional system. Data searching in the System of Studentsâ€™ Data Bank Score at Computer Science Department was using Brute Force Method by ten people that was randomly chosen. The questionnaire result of system testing was using Likert scale, with the result of final score was 83,33 or it could be stated that the System of Studentsâ€™ Data Bank Score at Computer Science Department by using Brute Force method was â€œVery Goodâ€.